Literature review and current trends on transfemoral powered prosthetics. (17th January 2018) - Lara-Barrios, Carlos M.; Blanco-Ortega, Andrés; Guzmán-Valdivia, Cesar H.; Bustamante Valles, Karla D.
Abstract: Transfemoral amputation is a common amputation procedure for the human lower limbs. Passive, semi-active, and active prosthetic devices are usually prescribed to amputees in order to restore their quality of life (QOL) according to their abilities. From an engineering perspective, prosthetic and normal gait analysis, actuator technology, and biologic prosthetic control strategies are some of the current objects of study on active lower limb prosthetic design which aimed to reduce potential biomechanical disorders such as gait asymmetry or elevated metabolic cost due to the use of passive prosthetic devices. The main goal of active prosthetic design is to deliver prosthetic assistance at biological levels. This paper reviews the latest developments of semi-active and active prosthetics for transfemoral amputees; as well as the common design considerations and efficiency assessments performed on active transfemoral prosthetics under development in recent years. Abstract :